Effect of Taper Design on Trunnionosis in Metal on Polyethylene Total Hip Arthroplasty - Tan, Sok Chuen; Teeter, Matthew G.; Del Balso, Christopher; Howard, James L.; Lanting, Brent A. (The Journal of arthroplasty, 2015)
This study examines how taper design affects corrosion and fretting at the head trunnion surface. All hip prostheses retrieved between 1999 and 2013 with 28mm/+0 heads were selected, resulting in 44 cobalt-chrome-on-polyethylene implants, representing six taper designs. Mean implantation time: 8.9±3.7years. The femoral head tapers were scored for fretting and corrosion using the Goldberg scale as both a combined score and by three zones (apex, central and base). There was no difference in age (P=0.34), BMI (P=0.29), or implantation time (P=0.19) between taper groups. The 11/13 taper had the highest combined corrosion and fretting score, but no difference (P=0.22) between groups for combined scores (P=0.22 for corrosion, P=0.19 for fretting). In a zone-specific analysis, the 11/13 taper had highest corrosion score at base zone (P=0.02). Taper design had a significant effect on corrosion at base of trunnion.